Interhemispheric interactions in visual word recognition: the role of multiple meanings - Kim, Sangyub; Nam, Kichun (Frontiers in Psychology, 2025)
IntroductionThe current study investigated the influence of the number of meanings on visual word recognition, with a particular focus on hemispheric dynamics.MethodsBy reanalyzing parafoveal Korean lexical decision data, we examined how words with a high versus low number of meanings affect right visual field advantage (RVFA) and bilateral redundancy gain (BRG).ResultsThe words with a greater number of meanings exhibited a stronger RVFA and reduced BRG compared to words with fewer meanings.DiscussionThe findings suggest that the facilitatory effects associated with multiple meanings are more pronounced in the left hemisphere (LH) than in the right hemisphere (RH). Furthermore, the increased lateralization of processing within the LH appears to diminish the need for interhemispheric interactions, leading to decreased coordination between the hemispheres. These results imply that the number of meanings in words shapes interhemispheric dynamics during visual word recognition. The implications of these findings are discussed in relation to theoretical models of visual word recognition and hemispheric differences in language processing.